2008
DOI: 10.3746/jfn.2008.13.2.122
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Aroma Composition of Chrysanthemum indicum L. Flower Oil

Abstract: The aroma constituents of Chrysanthemum indicum L. were separated by the hydro distillation extraction method using a Clevenger-type apparatus, and were analyzed by gas chromatography-mass spectrometry (GC/MS). The yield of Chrysanthemum indicum L. flower oil was 2.0% (w/w) and the color was light golden yellow. Sixty-three volatile flavor components, which make up 89.28% of the total aroma composition of the flower oil, were tentatively characterized. This essential oil contained 35 hydrocarbons (48.75%), 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…Although one ester from C. indicum was detected in this study, four esters in same the species were identified as trans-sabinene hydrate, cis-sabinene hydrate, trans-chrysanthenyl acetate, and bornyl acetate (Chang and Kim, 2009) …”
Section: Estersmentioning
confidence: 99%
See 4 more Smart Citations
“…Although one ester from C. indicum was detected in this study, four esters in same the species were identified as trans-sabinene hydrate, cis-sabinene hydrate, trans-chrysanthenyl acetate, and bornyl acetate (Chang and Kim, 2009) …”
Section: Estersmentioning
confidence: 99%
“…Although a total of 14 alcohols were detected from all taxa, their contents were different depending on the taxa. Chang and Kim (2009) reported that 12 alcohols were detected in flower of C. indicum, including 1, 8-cineole, chrysanthenol, isopinocarveol, borneol, terpinen-4-ol, endoborneol, carveol, eugenol, spathulenol, cedrol, vulgarol B, and -bisabolol. Choi et al (2006) reported 11 alcohols in flower of C. boreale, which was more than the number of alcohols detected from the same species in this study.…”
Section: Alcoholsmentioning
confidence: 99%
See 3 more Smart Citations